Why the Oxus? On the Majestic River of Arnold's 'Sohrab and Rustum'. (5th February 2018) - Taher-Kermani, Reza
Abstract: This essay is an examination of the structural significance of the river Oxus in Matthew Arnold's 'Sohrab and Rustum'. The river pervades Arnold's poem, not just in its celebrated 'coda'; its place in the poem's complex design was determined by a variety of ideological and aesthetic motives, and by Arnold's knowledge of, and response to, contemporary representations of the Oxus region and of Persia's place in ancient history and contemporary imperial politics. The aim here is to engage with the network of designs and discourses associated with the river in the nineteenth century in order to investigate the relationship between the conception of the poetic Oxus and the cluster of different notions that the river embodied in the discursive realms of the British imagination.